2017
DOI: 10.4140/tcp.n.2017.352
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Psychopharmacology Rounds in a Nursing Facility to Improve Antipsychotic Usage

Abstract: Implementing interdisciplinary psycho-pharmacology rounds in a nursing facility resulted in a reduction of inappropriate antipsychotic use and improved monitoring and documentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The majority of studies were located in the United States, UK and Australia with smaller numbers from the Netherlands, Canada and Belgium . Twelve papers reported randomised controlled trials, and five were non‐randomised controlled studies, with the remainder pre‐/post‐uncontrolled interventions conducted as service evaluations. Papers ranged in publication dates from 1978 to 2019, and all services reported positive outcomes with respect to their main aim.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies were located in the United States, UK and Australia with smaller numbers from the Netherlands, Canada and Belgium . Twelve papers reported randomised controlled trials, and five were non‐randomised controlled studies, with the remainder pre‐/post‐uncontrolled interventions conducted as service evaluations. Papers ranged in publication dates from 1978 to 2019, and all services reported positive outcomes with respect to their main aim.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen papers stated that the pharmacist delivering the service was a ‘consultant’, and twelve papers noted that the pharmacist was described as ‘clinical’ . Five papers reported that the pharmacist had completed an accreditation process, one of which described the training as consisting of consultation skills, identification of drug‐related problems, guidelines and how to create pharmaceutical care plans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional members of interdisciplinary teams, often tailored to the specific needs of facilities and populations, include nursing, 56 social workers and administration. 54 Since nursing assistants provide most of the direct resident care in nursing homes and are often with specific residents over extended time periods, 62 , 63 selectively including them when major plans of care and/or medications are proposed may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…One study was based in early intervention/psychosis services [86] and one based in other (mix of urban, non-urban and metropolitan centres) [71,72]. Pharmacists were involved to some extent in delivering the interventions across all studies, and those involved were mostly commonly specialist mental health/psychiatric pharmacists (n = 9) [73,79,83,[85][86][87][88][89][90] or clinical pharmacists (n = 9) [76,78,81,82,[91][92][93][94][95] (Table 4). Differences in terminology across studies due to differences in country of origin did not allow us to differentiate grades or qualification of pharmacists.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%